2015
DOI: 10.17535/crorr.2015.0026
|View full text |Cite
|
Sign up to set email alerts
|

The Baltic Dry Index and performance excellence in a crisis environment

Abstract: Abstract. This paper focuses on an approach to analyzing the relationship between the Baltic Dry Index (BDI) as the main indicator of the cyclical nature of the maritime market and the performance excellence of the representative shipping companies. Results have shown that there is a strong positive correlation between average annual BDI values and performance excellence indicators measured by the traditional adjusted Altman Z-score as well as the recent indicator, the Bex Index. BDI as the most comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The predictive results have been found valid both in the long as wells as short-term. Jurun et al ( 2015 ) find a strong positive correlation between annual BDI values and performance excellence indicators measured by the adjusted Altman z -score for maritime companies. Apergis and Payne ( 2013 ) analyzed the information and predictive content of BDI on a wide array of financial assets and macroeconomic parameters such as stock market returns, the interest rate of short-term and long-term bonds, commodity prices, and oil price.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive results have been found valid both in the long as wells as short-term. Jurun et al ( 2015 ) find a strong positive correlation between annual BDI values and performance excellence indicators measured by the adjusted Altman z -score for maritime companies. Apergis and Payne ( 2013 ) analyzed the information and predictive content of BDI on a wide array of financial assets and macroeconomic parameters such as stock market returns, the interest rate of short-term and long-term bonds, commodity prices, and oil price.…”
Section: Introductionmentioning
confidence: 99%
“…This index has been the subject of many research by both regional and foreign researchers. In their work, Jurun et al (2015) investigated the relationship between the BDI as an indicator of the cyclicality of the maritime market and the performance of selected shipping companies in the period from 1985 to 2013. Based on the conducted research, they concluded that there is a statistically significant correlation between the annual level of the BDI and the per-formance indicators of the selected shipping companies.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…and Kavussanos, Visvikis, and Menachof (2004) utilize co-integration analysis to examine the Forward Freight Agreements (FFA) predictability in the Panamax freight market. Jurun, Ratković, and Moro (2015) examined the relationship between the BDI, as the key indicator of economic and business activities, and the business results of companies, who deal whit sea transport (shipping companies). They have studied the relationship between the BDI and performance excellence of the representative shipping companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They studied the business performances of the selected shipping companies. Jurun et al (2015) used the adjusted Altman Z-score to measure business results. The conclusion of their study is that the BDI represents a good buying or selling signal for certain shares.…”
Section: Literature Reviewmentioning
confidence: 99%